Carbohydrates and their derivatives as corrosion inhibitors - Haque J.; Quraishi M.A. (My University, 2025)
Carbohydrates and their derivatives are widely studied as corrosion inhibitors for various metals and alloys. As, these compounds have a number of hydroxyl groups in the rings, which can easily donate electrons to the metal d-orbital and form a protective film over the metal surface, they resulted in showing good inhibition efficiency. This chapter covers the literature of some important inhibitors and discusses their synthesis process to find the best way of synthesis. The mechanism of corrosion inhibition also describes which is directly related to the electronic structure and molecular weight. Carbohydrates are the most abundant natural compounds, and hence considered as a green corrosion inhibitor. © 2022 John Wiley & Sons, Inc.